IoT Readiness Model for Urban Vocational School: Case Study in Indonesia - Novian Anggis Suwastika; Maslin Masrom; Qori Qonita; Misita Anwar (Qubahan Academic Journal)
The Internet of Things (IoT) holds significant potential to enhance vocational education, yet its implementation in this sector remains limited and has a low success rate. Ensuring organizational readiness is essential for successful IoT adoption. This study aims to develop a readiness model to assess the preparedness of urban vocational high schools (VHS) in Indonesia for IoT adoption. The research objectives are to identify key factors influencing VHS readiness, analyze their interrelationships, and determine priority areas for improvement to facilitate IoT adoption in urban VHSs. A quantitative online survey, covering ten factors and 54 indicators, was conducted with top management representatives from 159 urban VHSs in West Java, Indonesia. Data were analyzed through reflective measurement assessments, structural model assessments, and Importance-Performance Map Analysis (IPMA). The study identified four dimensions impacting VHS readiness for IoT adoption: environment, organization, technology, and people. The environmental dimension encompasses market forces, supporting industries, and government regulation, which in turn affect the organizational dimension, including governance and management support and financial readiness. The organizational dimension influences the technological dimension, represented by IoT infrastructure and data readiness and IoT operational readiness. The people dimension comprises technological pedagogical content knowledge and readiness to use technology, all of which directly or indirectly influence the primary factor, readiness to use IoT. Reflective assessments confirmed the validity and reliability of the indicators and factors, and structural model tests supported 12 of the 13 proposed hypotheses. IPMA results identified readiness to use technology and IoT infrastructure and data readiness as top priorities for improvement. This study offers valuable insights for VHS management in preparing for IoT adoption, contributing to the advancement of vocational education by synthesizing multiple foundational readiness frameworks. Additionally, it provides a reference for developing new models to assess and improve IoT readiness in educational settings or in other settings.